Exploring the Efficacy of Omega-3 Fatty Acid Supplementation in Dry Eye Disease: A Comprehensive Review - Anna Martyka; Martyna Kubicka Figiel; Nina Taborska (Journal of Education, Health and Sport, 2024)
Introduction